Intranasal delivery of cyclobenzaprine hydrochloride-loaded thiolated chitosan nanoparticles for pain relief. (23rd July 2013) - Patel, Deepa; Naik, Sachin; Chuttani, Krishna; Mathur, Rashi; Mishra, Anil K.; Misra, Ambikanandan
Abstract: The purpose of present investigation was to formulate and characterize the cyclobenzaprine HCl (CBZ)-loaded thiolated chitosan nanoparticles and assessment of in-vitro cell viability, trans-mucosal permeability on RPMI2650 cell monolayer, in-vivo pharmacokinetic and pharmacodynamic study of thiolated chitosan nanoparticles on Swiss albino mice after intranasal administration. A significant high permeation of drug was observed from thiolated chitosan nanoparticles with less toxicity on nasal epithelial cells. Brain uptake of the drug after 99m Tc labeling was significantly enhanced after thiolation of chitosan. CBZ-loaded thiolated chitosan NPs significantly reverse the N-Methyl-.-Aspartate (NMDA)-induced hyperalgesia by intranasal administration than the CBZ solution. The studies of present investigation revealed that thiolation of chitosan significantly reduce trans-mucosal toxicity with enhanced trans-mucosal permeability via paracellular pathway and brain uptake of a hydrophilic drug (normally impermeable across blood brain barrier) and pain alleviation activity via intranasal route.